2021
DOI: 10.1002/adma.202008119
|View full text |Cite
|
Sign up to set email alerts
|

Bioinspired Dual‐Mode Temporal Communication via Digitally Programmable Phase‐Change Materials

Abstract: Switchable optical properties are essential for numerous technologies including communication, anticounterfeiting, camouflage, and imaging/sensing. Typically, the switching is enabled by applying external stimulation such as UV light for fluorescence detection. In contrast, ground squirrels utilize spontaneous live infrared emission for fencing off predators as a unique way of communication. Inspired by this, live evolution of both optical and thermal images for temporal communication in which time is the enco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
61
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(61 citation statements)
references
References 27 publications
0
61
0
Order By: Relevance
“…The storage capacity of this system for large amounts of information was demonstrated based on the code methods under UV light irradiation, showing 1D, 2D, and 3D information recording capabilities. Zhao et al [13] demonstrated the temporal programming of information based on the digital light curing of a phasechanging elastomers. The optical contrast of the information could be tuned by the curing time, and the dual operating modes (optical and thermal) further extended the versatility.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The storage capacity of this system for large amounts of information was demonstrated based on the code methods under UV light irradiation, showing 1D, 2D, and 3D information recording capabilities. Zhao et al [13] demonstrated the temporal programming of information based on the digital light curing of a phasechanging elastomers. The optical contrast of the information could be tuned by the curing time, and the dual operating modes (optical and thermal) further extended the versatility.…”
Section: Introductionmentioning
confidence: 99%
“…Zhao et al. [ 13 ] demonstrated the temporal programming of information based on the digital light curing of a phase‐changing elastomers. The optical contrast of the information could be tuned by the curing time, and the dual operating modes (optical and thermal) further extended the versatility.…”
Section: Introductionmentioning
confidence: 99%
“…The decryption of information in stimuli‐chromic materials driven by irradiation, temperature and osmotic pressure is relatively slow, so the stored information has enough time to be identified and read. Whereas, time‐resolved encryption has been achieved only in limited research reports, in which the information appears at a specific time domain, and would disappear afterwards [8a,c] . Although information encryption technology by time coding has great potential, it is still nascent.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the properties of polymers can be changed easily by adjusting their chain structure, which was a much incomparable advantage of other materials. 28 For example, compared to uncross-linked materials, highly cross-linked materials are more challenging to stretch but tend to break when stretched, which means that they will have high strength and lower elongation. At the same time, inspired by shellfish, which have a stiff sheath to protect the soft core inside from harm, we believe that constructing a core−sheath structure in the polymer could also adjust the polymer properties and bring tremendous benefits, and the structure can be prepared through constructing layers with different structures and properties.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Moreover, the properties of polymers can be changed easily by adjusting their chain structure, which was a much incomparable advantage of other materials . For example, compared to uncross-linked materials, highly cross-linked materials are more challenging to stretch but tend to break when stretched, which means that they will have high strength and lower elongation.…”
Section: Introductionmentioning
confidence: 99%